2016
DOI: 10.1016/j.cub.2016.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational cues modulate the shape of defensive peripersonal space

Abstract: SummaryThe potential damage caused by an environmental threat increases with proximity to the body, so animals perform more effective and stronger defensive responses when threatening stimuli occur nearby the body, in a region termed the defensive peripersonal space (DPPS) 1, 2. We recently characterized the fine-grained geometry of the face’s DPPS by recording the enhancement of the blink reflex elicited by electrical stimulation of the median nerve (hand-blink reflex, HBR), when the hand is closer to the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 11 publications
5
27
1
Order By: Relevance
“…Moreover, the results we observed were not reflected in a general facilitation of tactile RTs, but were specific to the D2–D4 sound‐distance range, where the boundary of PPS was identified in Experiment 1. Indeed, PPS boundary changes that depend on the direction of constant gravitational vestibular input have been observed before by (Bufacchi & Iannetti, ). Here we extend these results by demonstrating the contribution of rotational vestibular signals to dynamic remapping of PPS.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Moreover, the results we observed were not reflected in a general facilitation of tactile RTs, but were specific to the D2–D4 sound‐distance range, where the boundary of PPS was identified in Experiment 1. Indeed, PPS boundary changes that depend on the direction of constant gravitational vestibular input have been observed before by (Bufacchi & Iannetti, ). Here we extend these results by demonstrating the contribution of rotational vestibular signals to dynamic remapping of PPS.…”
Section: Discussionsupporting
confidence: 62%
“…We note that these authors reported a left–right symmetry in eye blink responses to tactile stimulation at the hand when positioned at various distances from the face (Bufacchi et al ., ). In addition to left–right symmetry, peri‐head space was elongated in an upward vertical direction for upright participants (Bufacchi & Iannetti, ; Bufacchi et al ., ) and this elongation remained oriented in the upward vertical direction even if the participant's head was tilted to one side (Bufacchi & Iannetti, ), indicating potential contributions of static vestibular (i.e., otolithic) signals to peri‐head space at rest. Thus, the present data show that in static, upright individuals the audio‐tactile boundary of peri‐head space is left–right symmetric.…”
Section: Discussionmentioning
confidence: 99%
“…These coordinate systems are also determined, and re-weighted based on multisensory input ( Sereno and Huang, 2014 ). For example, the (predominantly) parietal body and face centred maps of personal space integrate visual and proprioceptive cues ( Huang et al., 2012 ; Bernier and Grafton, 2010 ; Sereno and Huang, 2006 ) and recent evidence suggests that these space fields can even be modulated by gravitational cues ( Bufacchi and Iannetti, 2016 ). The OPM technology, and its resilience to subject motion would allow one to non-invasively study millisecond resolved integration of these multiple sensory cues in both healthy participants and (for example) patients with spatial neglect.…”
Section: Discussionmentioning
confidence: 99%
“…Animals respond to stimulus more strongly when the stimulus takes place in close proximity to the body, within the DPPS region (Graziano and Cooke 2005). A recent study mapped the face's DPPS and found asymmetries in its geometry: the face's DPPS is projected forward (as opposed to backward) and upward (Bufacchi and Iannetti 2016). In line with Campbell's view, while the forward-backward asymmetry depends on the bodily frontward-backward axis (so that if the subject lies down the DPPS is still larger before the subject's head than behind it), the up-down asymmetry depends on gravity and not on the subject's body (so that if the subject lies down, looking up or looking sideways, the DPPS becomes larger towards the ceiling, not towards the "top" of the subject's longitudinal axis).…”
Section: Self-location and Self-consciousnessmentioning
confidence: 99%